The Management Programs of Aceh Tengah Educational Board Chairman in Improving the Quality of Elementary Education - Arnanda, Sabri; Murniati, Murniati; Usman, Nasir (Jurnal Pendidikan Progresif, 2020)
The Management Programs of Aceh Tengah Educational Board Chairman in Improving the Quality of Elementary Education. Objectives: The purpose of this research is to describe the planning, implementation strategy, and evaluation of the management programs of Aceh Tengah Educational Board Chairman in improving the quality of elementary education. Methods: Data collection using qualitative methods and data collection techniques through: Observation, interviews and documentation studies. The research subject is head of Education office, head of field, school principal. Findings: The results showed that planning was formulated through the musrenbang and the results of the evaluation of the previous period and involving government, MPD and community leaders. The strategy of implementing the program by involving the whole field, by providing the development of tasks according to their respective fields, such as training to improve the quality of educators ‘resources, improvement of facilities and infrastructure such as computerized and digitisation, and improvement of administrative services such as ease of access to program and ease of communication.Keywords: management, educational board chairman, quality education.DOI: 10.23960/jpp.v10.i1.202010